Molecular cloning and gene expression of desaturases and elongases in embryos, larvae, and adults of bay snook Petenia splendida (Cichliformes: Cichlidae) - Luis Daniel Jiménez-Martínez; Gloria Gertrudys Asencio-Alcudia; Carlos Alfonso Álvarez-González; Alejandra del Carmen Castillo-Collado; Vicente Morales-Garcia; Carina Shianya Alvarez-Villagomez; Candelario Rodríguez-Pérez; Rafael Martínez-García; César Sepúlveda-Quiroz; Graciela María Pérez-Jiménez (Neotropical Ichthyology)
Abstract The bay snook (Petenia splendida) belongs to the family Cichlidae, distributed in the southeastern region of Mexico and Central America, and it is a very important cichlid at a commercial level. Despite their potential for aquaculture, little information exists on their metabolic pathways related to physiology and nutrition. This study focuses on the expression of the fatty acid desaturases (fads2) and elongases (elovl4b and elovl5) genes in embryos 0 days post-hatching (dph) and larvae of 5, 10, 15, 20, 25, and 30 dph. Additionally, the differential expression of these genes was analyzed in the liver, intestine, kidney, muscle, heart, testes, gills, stomach, pancreas, brain, and adipose tissue in adult fish. Our study utilized specific qPCR primers designed for fads2, elovl4b, and elovl5 to detect the expression of these genes. We found the highest expression were observed in larvae at 20 dph and adults, predominantly in the liver and intestine of the three genes tested. Importantly, our results showed that the desaturase and elongase genes are differentially expressed in the tissues of adults of P. splendida, and their expression fluctuates during larval development.